Biologiczne skutki zróżnicowania społecznego ludzkich populacji szkieletowych z terenu Polski w okresie feudalnym. Aspekt morfologiczny - Kozak, Jerzy (Polskie Towarzystwo Antropologiczne, 1993)
BIOLOGICAL EFFECTS OF SOCIAL STRATIFICATION AMONG HUMAN SKELETAL POPULATIONS FROM FEUDAL POLAND. THE MORPHOLOGICAL ASPECT. In the study, the metrical traits of 30 skeletal populations from 9/10-19 c. Poland were analized, using the multi-trait method of principal components. The study attempts to determine the nature and strength of the connection between a changing social structure and one of the factors which shaped it (i.e. urbanizatin) and the morphological picture of human groups.
BIOLOGICAL EFFECTS OF SOCIAL STRATIFICATION AMONG HUMAN SKELETAL POPULATIONS FROM FEUDAL POLAND. THE MORPHOLOGICAL ASPECT